Skin Immunosenescence and Type 2 Inflammation: A Mini-Review With an Inflammaging Perspective - Chen, Bangtao; Yang, Jing; Song, Yao; Zhang, Daojun; Hao, Fei (Frontiers in Cell and Developmental Biology, 2022)
Skin-resident stromal cells including keratinocytes, fibroblasts and adipocytes, and immune cells including Langerhans cells, dendritic cells, T cells and innate lymphoid cells together with their functional products work in concert to ensure the realization of skin barrier immunity. However, aging-induced immunosenescence predispose the elderly to pruritic dermatoses including the type 2 inflammation-mediated. Inflammaging, characterized by chronic low-level of pro-inﬂammatory cytokines released from senescent cells with senescence-associated secretory phenotype (SASP), may drive immunosenescence and tangle with type 2 inflammatory dermatoses. Present mini-review summarize current evidence on immunosenescence and type 2 inflammation in skin, and further focus on future needs from an inflammaging perspective in order to clarify their complexity.